Mobile stance-taking in nature: an exploration of gaze patterns during assessments of objects in nature - Laner, Barbara (Frontiers in Psychology, 2025)
In this paper, I examine the interactional dynamics of walkers assessing entities in nature, focusing on gaze behavior during these sequences. The analysis is based on a corpus of 10 hiking pairs who walked through the Black Forest National Park while wearing mobile eye-tracking glasses to record their gaze behavior and verbal practices. Using a combined quantitative and qualitative approach, the research identifies gaze patterns in 127 sequences and highlights the role of bodily-visual practices. Contrary to existing literature, the findings indicate that mutual gaze in this setting is not used to mark affiliation but instead occurs only during strong disagreements about initial assessments. During agreements, walkers maintain a triangular position, both gazing at the assessable object without looking at each other. Thus, in this context, gazing at each other serves different interactional purposes, as this study will demonstrate.